"Indian disease": on the pathogenic principle of alterity and the modes of transformation in an Amazonian cosmology - Barcelos Neto, Aristóteles (2006)
During my field work among the Wauja Indians of the Upper Xingu, I collected several  narratives about local people who had suffered animal transformations when they were severely ill. Most of them returned to their human condition after the attention of highly specialized shamans and ritual singers and dancers. This article describes the series of transformations between humans and non-humans in  the Wauja cosmology and discusses how the attributes of humanity, animality and monstrosity are distributes and set in relation.